Volatile Glycosylation in Tea Plants: Sequential Glycosylations for the Biosynthesis of Aroma β-Primeverosides Are Catalyzed by Two Camellia sinensis Glycosyltransferases - Ohgami, Shoji (Plant Physiol, 2015)
Tea plants (Camellia sinensis) store volatile organic compounds (VOCs; monoterpene, aromatic, and aliphatic alcohols) in the leaves in the form of water-soluble diglycosides, primarily as β-primeverosides (6-O-β-d-xylopyranosyl-β-d-glucopyranosides). These VOCs play a critical role in plant defenses and tea aroma quality, yet little is known about their biosynthesis and physiological roles in planta. Here, we identified two UDP-glycosyltransferases (UGTs) from C. sinensis, UGT85K11 (CsGT1) and UGT94P1 (CsGT2), converting VOCs into β-primeverosides by sequential glucosylation and xylosylation, respectively. CsGT1 exhibits a broad substrate specificity toward monoterpene, aromatic, and aliphatic alcohols to produce the respective glucosides. On the other hand, CsGT2 specifically catalyzes the xylosylation of the 6′-hydroxy group of the sugar moiety of geranyl β-d-glucopyranoside, producing geranyl β-primeveroside. Homology modeling, followed by site-directed mutagenesis of CsGT2, identified a unique isoleucine-141 residue playing a crucial role in sugar donor specificity toward UDP-xylose. The transcripts of both CsGTs were mainly expressed in young leaves, along with β-PRIMEVEROSIDASE encoding a diglycoside-specific glycosidase. In conclusion, our findings reveal the mechanism of aroma β-primeveroside biosynthesis in C. sinensis. This information can be used to preserve tea aroma better during the manufacturing process and to investigate the mechanism of plant chemical defenses.